Optimalisasi Sampah Melalui Teknologi Biopori di Kelurahan Kota Besi Hilir - Muhammad Fauzan; Sritanti; Dina Kumala Sari; Lutfi Almadani; Desi Lestari; Khalimatus Sa'diah; Risa Amanda (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2025)
In waste management, the general practice in many villages still focuses on landfilling waste which is then thrown into final disposal sites. Apart from that, burning waste is often used as an alternative to reduce the volume of existing waste. However, this method causes negative environmental impacts such as increased air pollution and soil damage around village areas. This article, with the title